Tephrology of the 1932 eruption of the Quizapú volcano in the region of Laguna Llancanelo, Payenia (Mendoza, Argentina) (Latin American Journal of Sedimentology and Basin Analysis, 2021)
Tephrology is a broad term that comprises all the aspects related to “tephra” studies (stratigraphy, chronology, petrology, sedimentology, chemistry, Froggat and Lowe, 1990; Lowe and Hunt, 2001) (Fig. 1). In Argentina, tephrological studies have significantly increased recently as a result of the increment in the Southern Andes volcanic activity affecting the country in the last two decades (E.g.: Corbella et al., 1991a,b; Stern, 1991; Mazzoni and Destéfano, 1992; Nillni et al., 1992; Gonzalez Ferrán, 1993; Naranjo et al., 1993; Scasso et al., 1994; Nillni and Bischene, 1995; Haberle and Lumley, 1998; Villarosa et al., 2002; Kilian et al., 2003; Naranjo and Stern, 2004; Orihashi et al., 2004; Stern, 2004; Scasso and Carey, 2005; Daga et al., 2008; Watt et al., 2009; Martin et al., 2009; Leonard et al., 2009; Rovere et al., 2009, 2011; Wilson et al., 2009, 2012). The eruption of Quizapú volcano (Volcanic Complex Azul-Descabezado Grande, Province of Talca, Chile, 36,67°S-70,77°W, maximum height of 3788 m a.s.l.), that occurred on April 10, 1932, represented one of the largest eruptions worldwide in the 20th Century. It affected extensive regions of Argentina as well as many coastal areas of the Southwestern Atlantic Ocean as a result of the prevailing westerly winds, and specifically impacted dramatically in regions located nearby the source volcano (Department of Malargüe, Province of Mendoza, west-central Argentina, Fig. 2). The wide spreading of the resulting tephras and its easy reconnaissance in the field provides a great opportunity for detailed studies about the eruption and its products. Results on the eruptive aspects and tephras dispersion and deposition from this eruption were published by some authors (Lunkenheimer, 1932; Kittl, 1933; Walker, 1981, Hildreth and Drake, 1992, González Ferrán, 1993; Ruprecht and Bachmann, 2010; Ruprecht et al., 2012). In this contribution the sedimentological, mineralogical and chemical characteristics of the tephra deposits occurring at the Llancanelo Lake and surroundings, located 140 km east (downwind) of the Quizapú volcano, are studied based on grain-size, petrographic and electron microscope analysis (SEM) as well as semiquantitative chemical determinations by Energy Dispersive Spectrometer (EDS). The obtained results, when compared with the results of analyses performed by other authors in tephras from the 1932 eruption of the Quizapú volcano, allow attributing the studied tephra layer to this eruption. On these bases, diverse aspects related to the depositional and post-depositional aspects of the tephras are herein discussed, as well as some environmental changes produced by the eruption. On the other hand, this paper contributes to a systematic and comparative classification of volcanic hazard in health and society that serves as base-studies for better understanding other more recent Southern Andes eruptive events that affected Argentina (Hudson, Copahue, Chaitén, Llaima, Peteroa and Puyehue-Cordón Caulle volcanoes). The eruption of Quizapú volcano in 1932 was one of the most important events among a long history of activity of this volcanic complex (Smithsonian Institution, 2012). It had a plinian character and threw into the atmosphere enormous amounts of tephras varying between 5 and 30 km3 according to different authors (Kittl, 1933; González Ferrán, 1993; Hildreth and Drake, 1992; Ruprecht and Bachmann, 2010), producing a dramatic impact in society, agriculture and local economies in the downwind neighboring affected regions (Abraham and Prieto, 1993; González Ferrán, 1993). The tephra deposits were very uniform in thickness with a notable decreasing grain-size tendency with distance from the source volcano, ranging from 6 cm in neighboring areas and reaching silt and clay sizes around 100 km east (Kittl, 1933; Hildreth and Drake, 1992). The horizon of tephras was recognized as a regional level in a number of natural outcrops pits and excavations, as well as in sediment cores recovered from short drillings (Fig. 3). The tephra level was affected by compaction and post-depositional transformations after 80 years of burying and exposure to weathering and pedogenetic processes, although most of the original characteristics are very well preserved. The sedimentary sequence in which the tephra level is included was recognized regionally by surface and subsurface surveys based on geoelectrical methods and short drillings (Violante et al., 2010; Osella et al., 2010, 2011; de la Vega et al., 2012). The sequence is composed of light brown sandy-silty sediments of lacustrine and eolian origin with high volcaniclastic content and interbedding of buried soils and evaporites (Rovere et al., 2010a,b; D´Ambrosio et al., 2011).In some profiles (P19 and P42, Fig. 3) located in marginal areas east of the lake, the tephra layer overlies lacustrine deposits and is in turn covered by eolian deposits; this indicates that the lake borders were filled with tephra during the eruption and definitively desiccated, and were later covered by eolian deposits probably as a result of the aridity of the climate that followed the eruption. On the other hand, in the lacustrine plain west of the lake the tephra layer was not found; a possible explanation for this is either post-depositional erosive processes or not deposition, as some places could have been, at the moment of the eruption, part of the lacustrine body with higher water energy, and therefore the ash was dispersed without leaving any recognizable deposit. Northwest of the lake, the tephra deposit was found overlying a buried soil containing burned vegetation remains (profile P45, Fig. 3), suggesting high temperatures of the ash fall with consequent burning of vegetation, as it was also documented in other regions of the world (Carson et al., 1990; Seymour et al., 1993). In the lacustrine coastal plain of the lake, tephra layers were found overlying eolian deposits (profiles P5, P21 and P26, Fig. 3). Tephra´s grain-size indicates varied sizes between very fine and medium sand. Sediments are poorly sorted and statistical grain-size distributions (Table 1, Fig. 4) are bimodal with two well-marked populations separated at the size-range of 3-3,5 ? (88- 125 µm). Population 1 is coarser with mode between 1 and 2 ? (250 to 500 µm), whereas Population 2 is finer with mode between 4 and 7 ? (63 to 8 µm). This bimodal distribution is typical for distal tephras (Bonadonna and Houghton, 2005; Rose and Durant, 2009). The lower-sized population contains the “respirable particles” (PM10
Keywords: Tephras, Quizapú Volcano, Sedimentolo- Gy, Volcanic Impact, Llancanelo Lake.